A combined theoretical-experimental approach for modelling ductile fracture of cold-reduced G450 steel sheet. (September 2020) - Mai, Bac V.; Nguyen, Giang D.; Hancock, Gregory J.; Pham, Cao Hung
Abstract : A thermodynamics-based coupled damage-plasticity model for high strength cold-reduced steel is developed on the basis of a generic form, allowing the use of any yield criterion and damage evolution rule. The model possesses essential features of ductile failure, including large plastic deformation prior to fracture and the effects of both triaxiality and Lode angle on the failure. In conjunction with theoretical development, experimental work for both furthering the understanding of ductile fracture in high strength cold-reduced steel and validation of the proposed model under different loading conditions is also performed. In particular, advanced non-contact measurement techniques based on Digital Image Correlation (DIC) are used not only for characterising the material failure/data in both pre- and post-peak phases but also for calibration of parameters and validation of the proposed model. While the pre-peak hardening responses with homogeneous deformation can be described by a nonlinear hardening rule, in the post-peak regime, localisation of deformation before complete fracture requires the use of energy in both characterisation of the material failure and calibration of the model. In this sense, the essential work of fracture obtained from the experiments is linked with parameters controlling the fracture of the material and also used for a simple regularisation technique based on the concept of smeared deformation. The model responses are validated against experimental data in terms of both macro responses and evolving failure patterns, demonstrating good potential for applications in failure analysis of structures made of high strength cold-reduced steel.